Risk of Blindness in Rheumatoid Arthritis Patients: A Case Report - Ayu, Miranti Laras; Idrus, Elfa Ali (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2026)
Background: Peripheral ulcerative keratitis (PUK) is a serious inflammatory disorder of the juxtalimbal corneal stroma, characterized by epithelial defects, infiltration of inflammatory cells, and progressive thinning of the stroma, potentially resulting in vision loss. Rheumatoid arthritis (RA) is the most common systemic autoimmune condition linked to non-infectious PUK, responsible for about 34% of cases, with nearly half exhibiting bilateral involvement. Objective: This case report presents a patient with bilateral PUK associated with RA and highlights the importance of early diagnosis and timely management to prevent vision loss. Case presentation: A 43-year-old female presented with a 12-month history of blurred vision and progressive ocular pain. Physical inspection revealed a skin rash, swan neck deformity, boutonniere deformity, and hallux valgus on both legs. Ocular examination showed a crescent-shaped peripheral corneal ulcer with an epithelized iris prolapse in the right eye, and nasal corneal thinning with peripheral ulceration in the left eye. Irregular pupils and distinct lens morphology were also noted. Serological tests were positive for antinuclear antibodies (ANA) and rheumatoid factor (RF). Result: The patient was diagnosed with RA-associated PUK and started on systemic and topical corticosteroids. Treatment led to initial improvement in ocular inflammation and stabilization of corneal structure. Conclusion: RA is the most frequently associated autoimmune condition in PUK. Early recognition of systemic autoimmune disease in patients with peripheral corneal ulcers is critical. Timely multidisciplinary management involving internists and ophthalmologists can preserve vision and improve patient outcomes.